GENERALIZED MODEL OF THE ADS-B UNMANNED AERIAL VEHICLE DATA TRANSMISSION PROCESS IN A STEGANOGRAPHIC SYSTEM - Semenov, Serhii; Zhang, Minjian; Yenhalychev, Serhii; Smidovych, Leonid (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The subject of the article is a model of the ADS-B data transmission process of an unmanned aerial vehicle in a steganographic system using direct spectrum expansion technology. The aim of the publication is to improve the security of unmanned aerial vehicles with an integrated ADS-B system. Particular scientific tasks: analysis of basic methods of ADS-B format data protection; development of the scheme of ADS-B drone data transfer in steganographic system with the use of direct spectrum expansion technology; improvement of the model of ADS-B drone data transfer in steganographic system with the use of direct spectrum expansion technology; determination of qualitative and quantitative characteristics as well as security properties of ADS-B format data. The following research results were obtained: as the result of the scientific works analysis the hypothesis about the perspectives of the ADS-B format steganographic data protection usage was put forward; the scheme of an unmanned aerial vehicle ADS-B data transmission in the steganographic system with the usage of the direct spectrum spreading technology was developed; the main safety properties as well as the safety parameters and characteristics of the ADS-B format information signal were formulated; the generalized model of an unmanned aerial vehicle ADS-B data transmission was further developed. This will improve the safety of UAVs. The advantages and disadvantages of the model were revealed, which allowed to determine the priority of further research and possible promising ways of solving the assigned tasks.